Hubungan Kepemimpinan Dengan Kinerja Tenaga Kesehatan di Puskesmas Labuhan Ruku Kec. Telawi, Kab. Batu-Bara - Amira, Annisa Puti; Nasution, Eka Madani; Nurhidayah, Nurhidayah; Rahma, Shinta; Mariani, Tia; Gurning, Fitriani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Leadership style is considered an important thing because the success or failure of an organization will be determined by the leadership style of a leader. Leadership style is a way that leaders can influence the work behavior of their employees. Apart from leadership style, there is also work motivation which is no less important to study because not many people realize that motivation has a first role in shaping behavior, as well as in influencing performance in an organization. Both of these things must be possessed by a head of a puskesmas to develop the performance of the health workers on duty at the puskesmas. This study used a qualitative research method, in which the approach method was through direct interviews at the Labuhan Ruku Health Center, Kec. Telawi, Kab. Coal. aims to find out how the leader's relationship with the health workers in this public health center. The results obtained from this study are that leaders and health workers have a fairly harmonious relationship. It was concluded that between the leaders and the health workers and staff at the Labuhan Ruku Health Center, Kec. Telawi, Kab. Batu-Coal has a very good relationship. This also affects the performance of health workers and staff to do their job properly and as optimally as possible. Keywords: Leaders, HRM, Pukesmas Health Workers